Guide to agricultural changes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Changing Public and Private Roles in Agricultural Service Provision. By D Carney. 1998. 90 pp. ISBN 0 85003 347 8 Overseas Development Institute Portland House Stag Place London, SW1E 5DP UK.